Deteksi Pencemaran Mikroplastik pada Air Lindi di TPA Piyungan Yogyakarta Indonesia - Inggita Utami; Agustina Agustina (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
Piles of plastic waste at the Piyungan Landfill in Bantul Yogyakarta can be a source of microplastics and endanger if they accumulate in the bodies of living things. Data collection on microplastic contamination in leachate ponds at the Piyungan landfill is essential because the leachate will go to the Opak River, which is still used by the community. This study aimed to analyze the abundance and polymer types of microplastics in the leachate at the Piyungan landfill. The study was conducted from January to April 2021. Leachate samples were taken at the inlet pond (before treatment) and outlet pond (after treatment). The research stages include leachate sampling, filtering particles, drying samples, density separation, separation with organic compounds, and filtering supernatants containing microplastics. Identification of microplastics was carried out visually using a microscope, while the identification of polymer types was determined by the Fourier-transform infrared streptoscopy test. The data were analyzed quantitative descriptively, and inferentially to compare the average abundance value and determine the correlation between microplastic abundance and abiotic parameters. The analysis results showed the abundance of microplastics in the inlet pool of 154.8 Â± 21.22 particles/L while in the outlet pool of 135.60 Â± 12.18 particles/L. According to the T-paired test, it was found that the abundance of microplastics in the two ponds was not significantly different. Water temperature correlates with the abundance of microplastic in the leachate. The identified polymer types are Polystyrene (PS), Polyethylene (PE), and Polyvinyl Chloride (PVC), which are commonly used as raw materials for single-use plastic, food containers, and leachate sewer pipes. This study concludes that in the leachate at the Piyungan landfill, the highest microplastic was found in the inlet pond with polymer types, namely Polystyrene (PS), Polyethylene (PE), and Polyvinyl Chloride (PVC). Therefore, the Yogyakarta government needs to increase the leachate processing process to decompose this microplastic and not pollute the Opak river as a leachate disposal channel for the Piyungan landfill.